1997
DOI: 10.1115/1.2841112
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Periodic Wake Passing on Film Effectiveness of Discrete Cooling Holes Around the Leading Edge of a Blunt Body

Abstract: Detailed studies are conducted on film effectiveness of discrete cooling holes around the leading edge of a blunt body that is subjected to periodically incoming wakes as well as free-stream turbulence with various levels of intensity. The cooling holes have a configuration similar to that of typical turbine blades except for the spanwise inclination angle. Secondary air is heated so that the temperature difference between the mainstream and secondary air is about 20 K. In this case, the air density ratio of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Film effectiveness increases with increasing blowing ratio with a somewhat level off in increases as blowing ratio approaches 1.5. These results are consistent with results presented by Funazaki et al (1997) with similar hole geometry. Fig.…”
Section: Resultssupporting
confidence: 96%
See 1 more Smart Citation
“…Film effectiveness increases with increasing blowing ratio with a somewhat level off in increases as blowing ratio approaches 1.5. These results are consistent with results presented by Funazaki et al (1997) with similar hole geometry. Fig.…”
Section: Resultssupporting
confidence: 96%
“…There have been several studies on leading edge showerhead film cooling in the 0142-727X/$ -see front matter Ó 2007 Elsevier Inc. All past. Mick and Mayle (1988), Karni and Goldstein (1989), Mehendale and Han (1992), Ou et al (1992), Salcudean et al (1994), Ekkad et al (1998), Funazaki et al (1997), Cruse et al (1997), Ou and Rivir (2001) experimentally studied the leading edge showerhead film cooling problem and provided fundamental results that has helped designers provide better protection for the high heat load region. Recently, York and Leylek (2002a,b) studied leading edge film cooling using CFD.…”
Section: Introductionmentioning
confidence: 96%
“…Teng et al [19] found that a single row of film holes do not have a notable influence on the location of the boundary layer transition. Funazaki et al [20] showed that for M > 0.8, the local blowing ratio in the hole was very high causing the jet to lift-off the cooled surface. The momentum of the coolant jet being very low at low blowing ratios made it more susceptive to the influence of periodic wake.…”
Section: Review Of Literaturementioning
confidence: 98%
“…Some of the unsteady wake studies on cascade and leading edge geometries include Du et al [14,15] , Han et al [16] , Adami et al [17] , Dullenkopf et al [18] , Teng et al [19] , Funazaki et al [20] , Rodriguez et al [21] , Heidmann et al [22] , O'Brien and Capp [23] , Ou et al [24] , Mehendale et al [25] , and Wright et al [26] . The laminar-turbulent transition for varying mainstream turbulence was observed to be different by Du et al [14] with the trailing edge ejection compensating for the velocity deficit caused by the periodic wakes.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The deterioration of film cooling effectiveness due to an unsteady wake in the leading edge region was studied (using a spoke wheel) by Funazaki et al (1997) and Heidmann et al (2001). The use of shaped holes to improve film coverage has been studied by Reiss and Bölcs (2000), Falcoz et al (2006) and Gao and Han (2009).…”
Section: Leading Edge Film Coolingmentioning
confidence: 99%